Predictive direct power control of three-phase three-level four-leg unified power quality conditioner. (18th October 2021) - Bouzidi, Mansour; Barkat, Said
In this paper, a predictive direct power control for three-phase three-level four-leg unified power quality conditioner (UPQC) has been proposed. The proposed three-level four-leg UPQC is capable of simultaneous compensation for supply voltage and load current disturbances. The predictive active and reactive power controllers were synthesised using a new predictive model of four-leg UPQC. In addition, a new algorithm of three-level three-dimensional space vector modulation (3DSVM) was proposed to control a three-level four-leg inverter. The idea is to perform the different steps of 3DSVM in only one sector. Furthermore, the voltage-balancing control of common DC capacitors was achieved by controlling the shunt converter using a three-level 3DSVM equipped by a balancing strategy. Finally, the proposed control method of the three-level four-leg UPQC was verified and compared with direct power control (DPC) through simulation using MATLAB/Simulink under different operating conditions.